(untitled) (Journal of Management and Social Sciences, 2018)
Abstract Nigeria is a multi-ethnic, multi-lingual and multi religious nation and sadly all these diversities have impacted adversely on her socio-political existence. The events of 1966–1970 call to question the unity and continued existence of Nigeria as an ethnically segmented nation. The Federal Military Government led by General Yakubu Gowon (rtd.) established the National Youth Service Corps (NYSC) programme as a means of achieving national integration in the face of mutual suspicion and hostility. Adopting the descriptive analytical method, this paper identifies insecurity, general discontent among parents, inadequate facilities, poor funding, and rejection of corps members among others as challenges confronting the programme. The paper therefore recommends improved funding of the programme, greater and sincere fight against insecurity, ethical re-orientation and religious tolerance as panacea to the challenges being faced by NYSC.